Perbandingan Pijat Laktasi dan Pijat Oxytocin Terhadap Peningkatan Produksi ASI Pada Ibu Postpartum - Maryati Maryati; Amalia Indah Puspitasari (Jurnal Ners, 2025)
Breastfeeding is a skill that requires time and patience to meet the nutritional needs of babies, especially during the first six months. The coverage of exclusive breastfeeding in DKI Jakarta in 2023 is still low, around 65.63%, lower than the national average. Irregular breast milk production often makes mothers switch to formula milk, which can hinder exclusive breastfeeding and affect the growth and development of babies. Efforts to increase breast milk production and provision are through lactation massage and Oxytocin massage, both of these massage techniques can help increase breast milk production naturally and provide physical and emotional benefits for breastfeeding mothers.To determine the comparison between lactation massage and Oxytocin massage on increasing breast milk production in postpartum mothers at Maya Mom and Baby Care.Using Quasi Experimental Design with Non-equivalent Control Group Design. The sample consisted of 30 respondents selected using the Total Sampling technique. Data analysis was carried out using the Wilcoxon Range List statistical test. The results of the analysis in the group receiving Oxytocin massage obtained a Z-Score of -3.410b and a P-value <0.001 (p <0.05). While the lactation massage group obtained a Z-Score of -3.422b and a P-value <0.001 (p <0.05). These results indicate that Oxytocin massage is more effective and efficient than lactation massage in increasing breast milk production. There is a significant difference between lactation massage and Oxytocin massage in increasing breast milk production in postpartum mothers at Maya Mom and Baby Care in 2024. It is hoped that postpartum mothers can be more fluent in providing exclusive breastfeeding to their babies, which is very important to support optimal baby growth and development